Flood Modelling of the Dez River Basin, Iran, Using the Watershed Modeling System Software - Sadrolashrafi, Seyedeh Sara (2008)
Flood is one of the natural disasters which can take place in many areas. In this research, a framework which integrates the Geographic Information System (GIS) with the Watershed Modelling System (WMS) for flood modelling was developed. It also interconnects the terrain models and the GIS software, with standard hydrological and hydraulic models, including HEC-1, HEC-RAS, etc. The Dez River Basin (about 16213 km²) in Khuzestan province in Iran was the study area in view of the frequent occurrences of severe flash flooding. Three storms which had caused floods in, January 1993, March 1993 and December 2001 were chosen to examine the modelling framework. The WMS is found to be capable of flood modelling and producing flood map. Hydrologic models can be integrated with HEC-RAS for a complete flood plain analysis in the WMS Package. The model consists of a rainfallrunoff model (HEC-1) which converts excess precipitation to overland flow and channel runoff; watershed parameters are calibrated manually to perform a good simulation of discharge at three sub-basins. Also statistical analysis had been done for hydrologic model and the model efficiency found to be 50%- 97%. Steady state flow simulation was performed in HEC-RAS model through the river channel network based on the HEC-1, peak hydrographs. Error in prediction of water surface levels was found to be less than 5%. Based on hydrologic and hydraulic simulations, Flood hazard maps for floods recorded January (1993), March (1993) and December (2001) are produced for the Dez River Basin based on the state-of-the-art GIS in the WMS software. Finally, a sensitivity analysis of the model parameters was performed and the most sensitive parameters identified are Curve Number (CN) and initial rainfall abstraction (STRTL) respectively. The modelling framework presented in this study demonstrates the accuracy and usefulness of the WMS software for flash flooding control in semi arid region. The results of this research will benefit future modelling efforts by providing validated hydrological software to forecast flooding on a regional scale. This model was designed for the Dez River Basin, and this regional scale model could be used as a prototype for the model applications in other areas.